Aminoglycosides as potential inhibitors of SARS-CoV-2 main protease: an in silico drug repurposing study on FDA-approved antiviral and anti-infection agents - Mohammad Z. Ahmed; Qamar Zia; Anzarul Haque; Ali S. Alqahtani; Omar M. Almarfadi; Saeed Banawas; Mohammed S. Alqahtani; Keshav L. Ameta; Shafiul Haque (Elsevier, 2021)
Background: The emergence and spread of SARS-CoV-2 throughout the world has created an enormous socioeconomic impact. Although there are several promising drug candidates in clinical trials, none is available clinically. Thus, the drug repurposing approach may help to overcome the current pandemic. Methods: The main protease (Mpro) of SARS-CoV-2 is crucial for cleaving nascent polypeptide chains. Here, FDA-approved antiviral and anti-infection drugs were screened by high-throughput virtual screening (HTVS) followed by re-docking with standard-precision (SP) and extra-precision (XP) molecular docking. The most potent drug's binding was further validated by free energy calculations (Prime/MM-GBSA) and molecular dynamics (MD) simulation. Results: Out of 1397 potential drugs, 157 showed considerable affinity toward Mpro. After HTVS, SP, and XP molecular docking, four high-affinity lead drugs (Iodixanol, Amikacin, Troxerutin, and Rutin) with docking energies −10.629 to −11.776 kcal/mol range were identified. Among them, Amikacin exhibited the lowest Prime/MM-GBSA energy (−73.800 kcal/mol). It led us to evaluate other aminoglycosides (Neomycin, Paramomycin, Gentamycin, Streptomycin, and Tobramycin) against Mpro. All aminoglycosides were bound to the substrate-binding site of Mpro and interacted with crucial residues. Altogether, Amikacin was found to be the most potent inhibitor of Mpro. MD simulations of the Amikacin-Mpro complex suggested the formation of a complex stabilized by hydrogen bonds, salt bridges, and van der Waals interactions. Conclusion: Aminoglycosides may serve as a scaffold to design potent drug molecules against COVID-19. However, further validation by in vitro and in vivo studies is required before using aminoglycosides as an anti-COVID-19 agent.